Experimental determination of minimum capacitor for self-excitation of induction generators - Sibrahim, Madjid; Aissou, Said; Rouas, Rabah; Haddad, Salah; Benamrouche, Nacereddine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This article addresses the issue related to determining the minimum capacitor required for the self-excitation of an induction generator. The determination of the minimum capacitance required for the self-excitation of a self-excited induction generator has already been the subject of several previous studies. It has been shown that the minimum capacitance depends on the rotation speed and the remanent magnetism. The study carried out in this paper shows that, in addition to the rotation speed and the remanent magnetism, there is a third parameter that has an influence on the self-excitation process, which is the acceleration or, in other words, the rotation speed ramp-up. In this paper, several experimental self-excitation tests for different values of the rotation speed ramp-up are carried out, leading to new characteristics of the minimum self-excitation capacitance as a function of the rotation speed. The results obtained from simulation and experimental studies prove the efficacy of the proposed approach.